PENGARUH TINGKAT SUKU BUNGA, INFLASI, DEBT TO EQUITY RATIO, DAN UKURAN PERUSAHAAN TERHADAP YIELD OBLIGASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 - 2016 - Laras Nurul Listiawati; V. Santi Paramita (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This study aims to determine the effect of interest rates, inflation, debt to equity ratio and firm size on bond yields at companies listed on the Indonesia Stock Exchange. Previous research shows different results. Therefore, it is necessary to do a research to re-examine the influence of these four variables on bond yield. The population in this study are all corporate bonds listed and traded on Indonesia Stock Exchange in period of 2010 to 2016, amounting to 584 bonds. Based on purposive sampling criteria 88 bonds were sampled. The research hypothesis was tested using multiple regression. This study concludes that interest rate has a positive effect on bond yield, debt to equity ratio negatively affect bond yield, while inflation and firm size have no effect on bond yield.